Zimbabwean indigenous religions and political drama: the fast track-land reform and the fast track change to attitudes to nature, 2000-2008. - Taringa, Nisbert T.; Sipeyiye, Macloud (Sapes Books, 2019)
The paper focuses on the impact of the Fast Track Land Reform Programme (FTLRP) on attitudes to the environment. The central argument of the paper is that the FTLRP was a noble idea that was inappropriately pursued resulting in ecological harm through unrestricted wanton exploitation of the environment. There is no doubt that land was badly needed in Zimbabwe, but one would agree that the environment was one of the biggest losers in the ongoing battle for scarce natural resources. The paper proceeds by looking at the historical background to the land issue in a bid to demonstrate how the programme that was plausible was derailed by selfish interests of some individuals and or groups that sought to gain from the polarized political landscape. It treats the place of Indigenous Religions in the conservation of the environment and how they were later reappropriated for political expedience at the expense of the environment.